Síntese hidrotérmica de micro-ondas das nanoestruturas de a-Bi2O3 e Bi2O2CO3 e estudo das propriedades estruturais e eletroquímicas - Souza, Roberta de Castro (2016)
In the present work, we obtained nanostructures of bismuth oxide and oxy-carbonate and nanocomposite from the combination of these bismuth materials with reduced graphene oxide (RGO) by hydrothermal microwave assisted varying the synthesis conditions. The material structure was characterized by X-ray diffraction and Rietveld refinement, wich showed the formation of the monoclinic Bi2O3 phase and the tetragonal Bi2O2CO3, indicating a periodic structural organization at long range. Samples that remain longer in the reactor and nanocomposites prepared with 8 and 16 mg of GO are mixture of both monoclinic and tetragonal phases. The images of scanning electron microscopy by field emission indicated the influence of time and the synthesis route on the morphology of the particles formed. Different morphologies with rounded, plates and sheets shapes resulting from the influence of the synthesis time was observed for Bi2O2CO3 samples. Samples of a-Bi2O3 exhibited morphology of rods and nanocomposites showed no significant changes in the obtained morphologies. The vibrational modes of the bismuth oxide and oxy carbonate were characterized by indicating the phases were formed, and in addition, it was observed that GO is converted to RGO during thermal reduction process for the formation of nanocomposites. UV-vis spectra showed charge transference bands, due to band gap transitions of bismuth nanomaterials and allowed to obtain values of band gap for the samples. The method of synthesis used in the preparation of the samples has advantages in terms of high reactivity of the reagents, easy control of the solution or interface reactions, and mostly low air pollution and low power consume. Samples showed electrochemical properties, in which the electrochemical performance and measures of charge and discharge times depends on the quantities of graphene oxide used in the synthesis of materials, due to the cooperation between the double layer capacitance of graphene oxide and pseudo-capacitance of Bi2O3, which are responsible for important applications, especially in capacitors for energy storage, which specific capacitance values are higher than the values found in the literature, allowing to obtain capacitors with capacitance values of 9.25 F cm- .